Topological disorder of microstructure in fiber-reinforced polymer composites: Diffusion response - Jain, D.; Mukherjee, Abhijit; Kwatra, N. (SAGE Publications Ltd, 2015)
Influence of microarchitectural fiber matrix arrangement in representative volume element is studied to assess the effect of mass diffusion in the fiber-reinforced polymer composites. A novel approach has been proposed to illustrate the quantitative definition of the representative volume element heterogeneity using topological descriptor of clustering. Average fiber center distance from the fixed representative volume element center is described to compute the clustering in different representative volume elements, followed by finite element method simulation to model and visualize two-dimensional microstructures of fiber-reinforced matrix composites with moisture boundary conditions. The suggested topology descriptor shows good correlation with diffusion response in relation to saturation time, whereas a fair degree of correlation was observed for mass accumulation and mass flux characteristics. The results indicate that microstructural heterogeneity has a strong influence on typical moisture diffusion characteristics and hence, an overall diffusion-induced damage. The observations should serve as a clue to design the fiber-reinforced polymer composites with the moisture barrier properties.